Crosslinked Matrimid®-like polyimide membranes with unimodal network structure for enhanced stability and gas separation performance. (10th December 2021) - Li, Si; McGinness, Hannah; Wang, Tao; Guo, Ruilan
Abstract: Gas separation membranes have attracted academic and industrial attention, and crosslinking has been identified to be one of the most effective ways to enhance membrane stability. In this paper, a series of crosslinked Matrimid®-like films with unimodal network structures are prepared via thermally end-linking phenylethnyl-terminated BTDA-DAPI oligomers with well-controlled molecular weight ( i.e., 3000–15, 000 g/mol), wherein the crosslink density (the inter-crosslink chain length) of resulting unimodal networks is systematically varied by using oligomers with various molecular weight. Comprehensive characterizations of chemical structure, thermal properties, microstructures are performed. Pure-gas permeation measurements are performed focusing on H2 /CH4 and CO2 /CH4 separations as a function of crosslink density. In sharp contrast to the commonly observed permeability reduction in randomly crosslinked networks, all the crosslinked unimodal films, even when densely crosslinked, present markedly enhanced permeability and well-maintained ideal selectivity relative to the uncrosslinked linear counterpart, leading to almost horizontal movements towards upper bounds along with expectedly enhanced membrane stability. It is concluded that introducing bulky groups at the crosslink sites provide a practical means to counteract the densification effect induced by crosslinking and the construction of unimodal networks exemplifies a fundamentally new strategy to regulate the microstructure and property of crosslinked membranes for gas separations. Graphical abstract: Image 1 Highlights: Phenylethynyl-endcapped Matrimid® oligomers with controlled MW were synthesized. Crosslinked unimodal network membranes were prepared via end-linking oligomers. Phenylethynyl end-linking led to enhanced permeability and maintained selectivity.